Comparison of Panoramic, Lateral Skull Projection and CBCT Images in Detection of Mandibular Condyle Fractures - Cansu Köseoğlu Seçgin; Hazal Karslıoğlu; Gürkan Gür Gür; Sevil Vural; Kaan Orhan; Mehmet Özemre; Kıvanç Kamburoglu (Cumhuriyet University, 2021)
Objectives: Condyle fractures constitute 17.5-52% of all mandibular fractures. Our first aim was to investigate whether panoramic radiography or LSP images with lower radiation dose can be used instead of CBCT in the diagnosis of vertical condylar fractures. The second aim of the study was to compare observers' capabilities in diagnosing these fractures. Materials and Methods: A sample consisting of 15 fresh cadaver mandibles with 30 condyles frozen within 24 hours post-mortem was randomly selected. Vertical fractures from the lateral 2/3 of the condyle head with 0.5 (10 condyles) and 1mm (10 condyles) thickness were created using a fret saw. After creating condyle fractures, digital panoramic, LSP, and CBCT images were acquired. Two dentomaxillofacial radiologists with 15 years of experience, two dentomaxillofacial radiologists with five and seven years of experience, and two newly graduated dentists have evaluated the images. The success of the observers in diagnosing the vertical condyle fracture in each imaging method, intra-observer and inter-observer agreement was evaluated. Results: The success of all dentists in determining the condyle fractures using LSP images was higher than the success they achieved using panoramic images, but it was not sufficient. Using different imaging options with CBCT, all diagnoses made by new graduates and dentomaxillofacial radiologists with five and 15 years' experience were 100% compatible with the gold standard (AC1: 1 (1-1)). Conclusions: For the diagnosis of vertical condyle fractures, conventional techniques (panoramic and lateral jaw imaging methods) were found to be insufficient.